Identification and determination of succinyladenosine in human cerebrospinal fluid - Krijt, J; Kmoch, S; Hartmannová, H; Havlícek, V; Sebesta, I (Journal of chromatography. B, Biomedical sciences and applications, 1999)
Succinyladenosine (S-Ado) is a biochemical marker of adenylosuccinase deficiency--the genetic defect of purine de novo synthesis. S-Ado has been previously reported as normally undetectable in cerebrospinal fluid (CSF) of children not suffering from this defect. In present study, we employed solid-phase extraction and thin-layer chromatography for isolation of a compound with spectral and chromatographic characteristics identical to S-Ado from human CSF. The high-performance liquid chromatography-negative-ion electrospray ionization mass spectrometry analysis confirmed that the isolated compound is S-Ado. We established the reference values of S-Ado in CSF of children (1.1+/-0.4 micromol/l; mean +/- S.D; n = 26) by means of reversed-phase HPLC method on a C18 column with UV detection.
Keywords: Purine-Pyrimidine Metabolism, Inborn Errors; adenosin; vysokoúčinná kapalinová chromatografie; Child; dítě; Mass Spectrometry; reprodukovatelnost výsledků; referenční standardy; Reproducibility of Results; Chromatography, High Pressure Liquid; chromatografie na tenké vrstvě; Spectrophotometry, Ultraviolet; lidé; Humans; Reference Standards; hmotnostní spektrometrie; Adenosine; poruchy metabolismu purinů a pyrimidinů; Chromatography, Thin Layer; spektrofotometrie ultrafialová